Feelings aroused during the COVID-19 pandemic in the elderly accompanied by the Family Health Strategy (Research, Society and Development, 2022)
The present study aimed to analyze the feelings aroused during the COVID-19 pandemic in the elderly who are accompanied by the Family Health Strategy. Observational, qualitative and descriptive study, developed with elderly people in the rural area of ​​the municipality of Canto do Buriti-PI. The sample consisted of 18 elderly people and data collection took place in two stages: through a semi-structured questionnaire with results described in a table and a structured questionnaire with audio-recorded content, transcribed and analyzed in the IRaMuTeQ software. From the data collected, it was found that the participants had a mean age of 68 years, most were female, had not completed elementary school, had an income of up to two minimum wages, most were married, white and lived with up to three people. Through textual analysis, a dendrogram was generated with seven classes categorized by the researchers: (1) “concern about losing family members” (2) “concern about following restrictive measures”; (3) “feelings aroused during the pandemic; (4) “emotions and perceptions of risk” (5) “behavioral changes imposed with the new routine” (6) “fear of getting infected” (7) “uncertainties generated by the pandemic”. As for the word cloud, the most representative feeling was fear. It is concluded that deepening knowledge about changes in the mental health of the elderly is essential to reveal the impacts caused, their relationships and the intrinsic protective factors for the construction of essential guidelines and strategies in the prevention of mental illness.